Experimental Protocol for Color Difference Evaluation Under Stabilized LED Light - Sofiane Vernet; Eric Dinet; Alain Trémeau; Philippe Colantoni (Journal of Imaging)
There are two key factors to consider before implementing a color discrimination experiment. First, a set of color patches should be selected or designed for the specific purpose of the experiment to be carried out. Second, the lighting conditions should be controlled to eliminate the impact of lighting instability on the experiment. This paper addresses both of these challenges. It proposes a method to print pairs of color patches with non-noticeable color differences. It also proposes a method to stabilize the Spectral Power Distributions (SPDs) of a Light-Emitting Diode (LED) lighting system. Finally, it introduces an experimental protocol for a color discrimination study that will be performed thanks to the contributions presented in this paper.